Caregivers' burdens and its' association with activities of daily living performance of individuals with stroke: A cross-sectional study / Nur Syafrawa Nabihah Mohamad Razali ... [et al.] - Mohamad Razali, Nur Syafrawa Nabihah; Talib, Siti Salwa; Ahmad Roslan, Nor Faridah; Che Daud, Ahmad Zamir (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Stroke leads to disability and has become the leading cause of dependence in daily life activities. Caring of individuals with stroke requires a lot of energy, time and resources to fulfil the individuals' needs. This situation leads to burdens and strains to the caregivers. There is a limited study on the relationship between Activities of Daily Living (ADL) performance of stroke's individuals with caregivers' burdens in literature. Thus, the aim of this study was to examine the association between ADL performance of individuals with stroke and the caregivers' burdens. A cross-sectional study was conducted with 59 individuals with stroke and their caregivers aged ranged from 20 to 86 years old. It was found that there was no significant correlation between the ADL performance of the individuals with stroke and the caregivers' burdens. However, there was a significant association found between caregivers' burdens and the duration of having the stroke (p=0.030). This study suggests that caregivers' burden is not associated with dependency level in ADL of individuals with stroke, but the duration of having the stroke does.